Novel Use of a Social-Media-Based Survey to Detect Regional Differences in Management of Monochorionic–Diamniotic Twins - Pluym, Ilina D.; Paek, Bettina; Walker, Martin; Liu, Hui; Kwan, Lorna; Rao, Rashmi; Scibetta, Emily; Afshar, Yalda; Holliman, Kerry; Wong, Thalia; Platt, Lawrence D.; Han, Christina S. (American Journal of Perinatology, 2020)
Objective This study aims to evaluate the utility of social media to distribute a patient survey on differences in management and outcomes of monochorionic–diamniotic (MCDA) pregnancies.Study Design A cross-sectional survey was posted to an English-language MCDA twins patient-centered support group within the social media site, Facebook from April 2, 2018 to June 26, 2018. Subjects were recruited through a technique called “snowballing,” whereby individuals shared the survey to assist with recruiting. Patient reported data were analyzed using Chi-square and Kruskal–Wallis's tests to explore characteristics associated with surveillance and outcomes as related to region and provider type.Results Over 3 months, the post “reached” 14,288 Facebook users, among which 5,653 (40%) clicked on the post. A total of 2,357 respondents with MCDA pregnancies completed the survey. Total 1,928 (82%) were from the United States (US) and 419 (18%) from other countries. Total 85% of patients had co-management with maternal–fetal medicine (MFM), more in the US compared with the rest of the world (87 vs. 74%, p < 0.01). MFM involvement led to increased adherence to biweekly ultrasounds (91 vs. 65%, p < 0.01), diagnosis of monochorionicity by 12 weeks (74 vs. 69%, p < 0.01) and better education about twin–twin transfusion syndrome (90 vs. 66%, p < 0.01). Pregnancies with MFM involvement had a higher take-home baby rate for both babies (92 vs. 89%, p < 0.01) or for at least one baby (98 vs. 93%, p < 0.01) compared with those without MFM involvement.Conclusion A survey distributed via social media can be effective in evaluating real-life management and outcomes of an uncommon obstetrical diagnosis. This survey elucidates wide international variation in adherence to guidelines, management, and outcomes.
Keywords: Facebook; monochorionic diamniotic; social media; survey; web-based research; twins